2017
DOI: 10.1177/2325967117709250
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Autologous Chondrocyte Transplantation in the Knee: A Systematic Review of Mid- to Long-Term Clinical Outcomes

Abstract: Background:Matrix-assisted autologous chondrocyte transplantation (MACT) is a surgical treatment option for articular cartilage lesions of the knee joint.Purpose:To investigate mid- to long-term clinical outcomes of MACT in the patellofemoral (PF) and tibiofemoral (TF) joints.Study Design:Systematic review; Level of evidence, 4.Methods:A systematic review was performed by searching PubMed, Embase, and the Cochrane Library to find studies evaluating minimum 5-year clinical outcomes of patients undergoing MACT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 31 publications
1
50
0
1
Order By: Relevance
“…The authors criticized the heterogeneous description of failure among all studies and underlined the importance of a coherent definition of failure. Another systematic review looked at MACI outcomes in a 5-year follow-up period and found a significantly higher failure rate in the TF compared to the PFJ (12.4 vs. 4.7%) [ 23 •] (Table 1 )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors criticized the heterogeneous description of failure among all studies and underlined the importance of a coherent definition of failure. Another systematic review looked at MACI outcomes in a 5-year follow-up period and found a significantly higher failure rate in the TF compared to the PFJ (12.4 vs. 4.7%) [ 23 •] (Table 1 )…”
Section: Introductionmentioning
confidence: 99%
“…of patients Mean patient age in years (range) Mean follow-up (range) Defect size, mean in cm 2 Outcomes Gomoll et al [ 7 ••] IV ACI 110 33 (15–55) 90 months (48–192) 5.4 84% good or excellent results, 9 failures (8%) which were treated with partial or total arthroplasty von Keudell et al [ 21 ••] IV ACI 30 32 (15–49) 7.3 years (2–15) 4.7 Good to excellent results in 25 (83%) patients, fair in 4 (13%) patients, poor in 1 (3%) patient, and 3 failures which were treated with PF and bicompartmental arthroplasty Ebert et al [ 20 ••] III MACI 194 37.7 (TF) vs. 37.9 (PF) 2 years 3.1 (TF) vs. 3.0 (PF) MACI in PF and TF shows similar results when PF maltracking is corrected if needed Andriolo et al [ 22 ••] IV ACI 4294 29 (21–51) 5–12.3 years 4.4 Failure rate of 14.9% (0–42.5) at 86 months. 64.0% of failures happened in the first 12 months, 26.1% between the second and fifth year, and 9.9% after the fifth year Schuette et al [ 23 •] IV MACI 578 31.3–42.3 Minimum 5–10 years 2.3–5.3 All scores significantly improved compared to baseline. In total, 9.7% of all patients failed, including 4.7% of PF patients and 12.4% of TF patients .…”
Section: Introductionmentioning
confidence: 99%
“…Vascularized tissues are being produced, providing an opportunity to create complex tissues and organs [215,216]. New and improved ECMs or scaffolds such as biodegradable ECMs and polymers are available for many applications including cartilage and spinal cord repair [217][218][219]. Cells can deposit ECMs on scaffolds and later be removed through a decellularized process, leaving a graft that can be used for several applications [220][221][222].…”
Section: Manufacturing and Regulatory Process Considerationsmentioning
confidence: 99%
“…In 1994, Brittberg et al were the first to publish this procedure, in the New England Journal of Medicine. During the last 20 years, it has proven to be a significant clinical option 41 42 43 44 . In the meantime, it has become an alternative for traumatic defects, particularly in younger patients.…”
Section: Regenerative Medicine In Clinical Routinementioning
confidence: 99%